Detection of luxS gene expression under stressing factors for biofilm formation by Propionibacterium acidipropionici and Propionibacterium freudenreichii - Romero, Danitza Xiomara; Cárdenas, Oscar Víctor; Olguin, Víctor Hugo Cavero; Aliaga, María Teresa Álvarez (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2015)
Gene expression constitutes an important role in cellular communication, setting mechanisms for biofilm formation. Genes can be used as molecular markers to monitor viability, stability and maintenance of biofilm eg. in biofilm reactors, bioremediation and biotransformation frequently under stressing conditions to enhance or limit the biofilm formation. In the present study, no pathogenic microorganisms of industrial interest were used. Propionibacterium freudenreichiisubsp. shermanii DSM 4902T and P. acidipropionici DSM 4900Tstrains cannot produce biofilm in culture conditions previously reported. In this regard, chemical culture conditions were modified to stimulate biofilm formation in both strains and determine that under stressing conditions such as 0.6 M NaCl, 1.8 M glucose and 10 gL-1 yeast extract both Propionibacterium produce biofilm. Finally, luxS expression was identified in biofilm of both strains by modified fluorescent in situ hybridization expression (FISH expression).